Generation Rx: evaluation of medication misuse prevention education for older adults - Emptage, Ruth E.; Lovatt, Brittany S.; Sloan, Cynthia D.; Li, Junan; Downing, Molly N.; Summers, Katherine E. (Frontiers in Public Health, 2024)
Abstract Objective(s): Increased medication misuse over the last two decades has prompted extensive discussion about the lack of evidence-based and evidence-informed prevention education programs targeting the topic. As older adults are high utilizers of medications, this is an important population to reach with such educational programming. This study was designed to assess the change in knowledge and behavioral intentions of older adult participants after attending an educational session focused on safe medication use utilizing the Generation Rx Older Adult Toolkit (GROAT) resources. Methods: The Generation Rx team at The Ohio State University College of Pharmacy (OSU COP) partnered with The Ohio State University Extension offices (OSU Extension) across the state of Ohio to provide GROAT educational programming in their communities. OSU Extension Educators were trained via the standardized virtual training program, Generation Rx Ambassadors. Program participants were surveyed immediately before and after the educational events. Pre- and post-survey data was then analyzed to assess knowledge gain and behavioral intentions about safe medication practices, as well as program perception and program satisfaction. Results: Programming occurred between May 2022 and September 2022. In total, OSU Extension Educators collectively engaged 843 individuals in a prevention education program utilizing the GROAT materials. After excluding participants under 50 years of age, there were 297 pre surveys and 245 post surveys included in the data analysis. Knowledge gains from pre- to post- survey showed a significant increase in correct responses in seven of the eight questions asked regarding safe medication practices. All five questions evaluating behavioral intentions demonstrated positive results after the programming (P<0.001). Participants' perceptions and program satisfaction were also favorable. Conclusion: This study found through pre- and post-survey results that the Generation Rx Older Adult Toolkit programming delivered by Generation Rx trained OSU Extension Educators significantly increased older adult participants’ knowledge and favorably impacted behavioral intentions around safe medication use practices.